Pulmonary embolism and hemorrhage after displacement of angiographic catheter tip to pulmonary artery: A case report and literature review - Liangwei Xiong; Li Zhuo; Jianhua Zhang; Shaoyong Liang; Zongding Wang (Heliyon, 2024)
Pulmonary embolism and massive hemoptysis caused by intravascular foreign bodies have rarely been reported. We report a case of an end-stage renal disease patient in which the tip of the angiographic catheter fell off into the pulmonary artery during endovascular interventional opening when the patient underwent vascular access occlusion for dialysis. During the operation, the foreign body was displaced repeatedly and finally anchored to the posterior basal segment branch of the right lower pulmonary artery. A pulmonary embolism occurred during the operation, and massive hemoptysis and hemorrhagic shock occurred after anticoagulation and thrombolytic therapy. After receiving anti-shock and symptomatic treatment, the patient gradually recovered. After six months of follow-up, no pulmonary embolism or pulmonary infarction occurred. Our case report presents an alternative approach to extracting a foreign object from the pulmonary artery by locating the foreign object within the vascular terminations, without resorting to forceful removal. This method mitigates the potential risks of pulmonary embolism and bleeding associated with forceful extraction.